Adsorbent Preparation From Rice Husks Coated With Nanochitosan From Crab Shells - Lubis, Arinda Budiarti; Herlinawati, Herlinawati (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Rice husks are a waste that is often found, containing 50% cellulose and 25-30% lignin so it has the potential to be used as an absorbent material. Therefore, rice husks can be used to make active carbon. The carbon activation process using HCl is preferred because compared to other acids, carbon activated with HCl shows better adsorption capacity. Chitosan comes from chitin found in crustaceans such as crabs. The crab shells are then processed to obtain chitosan. This research aims to produce rice husk adsorbent coated with nanochitosan from crab shells. Characterization in this study used FTIR which showed the presence of N-H groups as a characteristic of chitosan at a wavelength of 3354.42 cm-1. PSA analysis shows nano-sized chitosan with a size of 58.15 nm. Coating rice husk activated carbon with crab shell chitosan has produced a suitable adsorbent and can be used for further testing..